Efficacy of Stereotactic Body Radiotherapy in Patients With Hepatocellular Carcinoma Not Suitable for Transarterial Chemoembolization (HERACLES: HEpatocellular Carcinoma Stereotactic RAdiotherapy CLinical Efficacy Study) - Brunner, Thomas B.; Bettinger, Dominik; Schultheiss, Michael; Maruschke, Lars; Sturm, Lukas; Bartl, Nico; Koundurdjieva, Ivana; Kirste, Simon; Neeff, Hannes P.; Goetz, Christian; Nicolay, Nils Henrik; Ihorst, Gabriele; et al. (Frontiers in Oncology, 2021)
The aim of this prospective observational trial was to evaluate the efficacy, toxicity and quality of life after stereotactic body radiation therapy (SBRT) in patients with hepatocellular carcinoma (HCC) and to assess the results of this treatment in comparison to trans-arterial chemoembolization (TACE). Patients with HCC, treated with TACE or SBRT, over a period of 12 months, enrolled in the study. The primary endpoint was feasibility; secondary endpoints were toxicity, quality of life (QOL), local progression (LP) and overall survival (OS). Between 06/2016 and 06/2017, 19 patients received TACE and 20 SBRT, 2 of whom were excluded due to progression. The median follow-up was 31 months. The QOL remained stable before and after treatment and was comparable in both treatment groups. Five patients developed grade ≥ 3 toxicities in the TACE group and 3 in the SBRT group. The cumulative incidence of LP after 1-, 2- and 3-years was 6, 6, 6% in the SBRT group and 28, 39, and 65% in the TACE group (p = 0.02). The 1- and 2- years OS rates were 84% and 47% in the TACE group and 44% and 39% in the SBRT group (p = 0.20). In conclusion, SBRT is a well-tolerated local treatment with a high local control rates and can be safely delivered, while preserving the QOL of HCC patients.